The Effect of Sales Growth and Total Asset Turnover (TATO) on Stock Return at PT Kimia Farma Tbk. - Novita Suciyati; Aliah Pratiwi; Wulandari (Yayasan Amerta Insan Unggul, 2026)
This study aims to examine the effect of Sales Growth and Total Asset Turnover (TATO) on Stock Returns at PT Kimia Farma Tbk during the 2014–2023 period. The research is motivated by the inconsistency between the company’s financial performance and stock price fluctuations, particularly in the pharmaceutical sector, which is highly sensitive to market sentiment and external shocks. This study employs a quantitative approach with an associative design using secondary data derived from the company’s annual financial statements. The analytical method applied is multiple linear regression, supported by classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests, as well as hypothesis testing through t-tests and F-tests. The results show that Sales Growth and TATO do not have a statistically significant effect on Stock Returns, either partially or simultaneously. The coefficient of determination (R²) indicates that 34.7% of the variation in stock returns can be explained by these variables, while 65.3% is influenced by other factors not included in the model. These findings suggest that stock return dynamics are not solely driven by internal financial performance but are also significantly influenced by external factors such as market sentiment, macroeconomic conditions, and investor behavior. This study contributes to the literature by highlighting the limitations of traditional financial ratios in predicting stock returns and emphasizes the need for a more comprehensive analytical approach. Practically, the findings encourage companies to enhance strategic innovation and investor communication while guiding investors to adopt broader evaluation criteria in investment decision-making.